Analysis of the Utilization of the SI-PAS OKE Application for Synchronizing Data on Junior High School Education Facilities and Infrastructure in Mojokerto City - Nadya Anggraini; Yulita Dhania Werdianti; Rizky Putri Eswanto; Aulia Tiarista; Nuansa Bayu Segara; Asih Putriningrum Hastari (Sean Institute, 2026)
This study aims to analyze the SI-PAS OKE application as a digital innovation to improve the accuracy and synchronization of data on all junior high school infrastructure facilities in Mojokerto City. The main problem found is the data mismatch between manual school recording and Regional Property Data, which causes low accuracy, slow reporting, and planning that is not based on factual data. This study uses a descriptive qualitative method. Data collection was carried out through library research to examine relevant theories, and was strengthened by in-depth interviews with application developers, observations, and documentation during the application implementation period, namely from August to October 2025. The main research instrument involved comparative data between BMD data, school manual data, and data synchronized in the SI-PAS OKE application, as well as trial results in three schools (SMPN 3, SMPN 7, and SMPN 4). Data analysis techniques were carried out by reviewing, grouping concepts, and interpreting the results of data collection to describe in depth the use of the application. This research shows that this application is able to eliminate the GAP DATA which previously reached more than 10% and produces full synchronization between BMD data, manual data, and application data. This finding is in accordance with the SCOT theory that technology develops in response to social needs, especially in the need for data integration.